Pentahelix Model In Community-Based Tourism Development In Situbondo District - Sri Yuniati; Djoko Susilo; Pandu Wirayudha; Nandania Isra’iya (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2023)
Community-based tourism is part of sustainable tourism development. Community-based tourism involves the community as the main actor in its management and aims to increase economic and industrial activities, preserve culture, and improve the economies of local communities. This research aims to describe the pentahelix model in community-based tourism development in Situbondo Regency, East Java. The research method used is qualitative research with a case study approach. The research data were collected from observations, interviews and documentation. The research data were analyzed descriptively and qualitatively. The results showed that community-based tourism development in Situbondo Regency has involved collaboration among actors in the pentahelix model, namely local government, academics, industry and business, the community, and mass media. The local government acts as a regulator in formulating policies related to community-based tourism management. The community, as the manager of community-based tourism, prepares institutional planning and organization and builds cooperation with academics and businesses in developing innovation, knowledge and competence in human resources and business management. The mass media play a role in the promotion and marketing of community-based tourism. However, the cooperation between the actors in the pentahelix model has not been optimal, especially with the limited involvement of industry/business and mass media. There is a need to strengthen cooperation among actors and to strengthen the institutional capacity of the community as a manager of community-based tourism.